Closing the Gap: An Empirical Evidence on Firm's Innovation, Productivity, and Export - Viroj Jienwatcharamongkhol; Mohammad H. Tavassoli (European Regional Science Association (ERSA), 2013)
It is well known that exporters are productive firms. But the source of their productivity is left unexplained. This paper aims to endogenize the productivity heterogeneity of exporting firms by incorporating innovation in a structural model framework. In doing so, we close the gap between the innovation-productivity and productivity-export literature. Two waves of Swedish Community Innovation Survey (CIS) are merged. This allows for a dynamic setup that takes into account the proper lags from innovation input to innovation output and also from innovation output to productivity and export. The applied framework corrects for selectivity, simultaneity, and potential endogeneity biases. The main findings highlight that exporters are productive firms with innovation output in the past, which in turn was driven by prior R&D and other innovation activity investments.
Keywords: C31; L60; O31; 330